Palliative health care for amyotrophic lateral sclerosis patients - M. N. Zakharova; I. A. Avdunina; E. V. Lysogorskaia; A. A. Vorobyeva; M. V. Ivanova; A. V. Chervyakov; A. V. Vasiliev (Нервно-мышечные болезни, 2015)
This article is a critical review of palliative care for ALS patients in Russia. The authors summarize the principal European guidelines, analyze local practice guidelines regarding palliative care, present their experience in ALS patients care in a multidisciplinary team (projectof the Orthodox service "Miloserdie"). Аuthors describe the main approaches for ALS symptom management available in Russia (including swallowing difficulties, breathlessness, pain, difficulties in communication).